ADHS im Erwachsenenalter und Borderline-Persönlichkeitsstörung: eine Pilotstudie zu den Unterschieden im Bindungsstil und frühkindlichen Traumatisierungen = Adult ADHD and borderline personality disorder : a pilot study on differences in attachment and early traumatization - Schmidt, Anne-Christin; Gablonski, Thorsten-Christian; Wladika, Wolfgang; Oberlerchner, Herwig; Lex, Claudia; Andreas, Sylke (Zeitschrift für psychosomatische Medizin und Psychotherapie, 2018)
Adult ADHD and borderline personality disorder: A pilot study on differences in attachment and early traumatization Objective: Attention-deficit/hyperactivity disorder (ADHD) in adulthood and borderline personality disorder (BPD) share commondiagnostic criteria.The present study examined how ADHD in adulthood can be distinguished from BPDregarding attachment style and traumatic experiences. - METHOD: The sample consists of N = 30 persons with 50% (n = 15) ADHD patients and 50% (n = 15) BPD patients. The patients were asked to fill out different questionnaires to investigate the criteria for specific symptoms. - RESULTS: The results show that most of the patients are insecurely attached. In addition, 80% of both the ADHD and BPD sample claimed traumatic experiences in their childhood or adolescence. Most frequently, patients reported traumatisation following emotional neglect and emotional abuse. No group-specific differences concerning traumatic experiences and the individual attachment style were determined. - CONCLUSION: The etiological factors attachment style and traumatic experiences are not suitable for differentiating ADHD in adulthood and BPD.